SPE Oklahoma City Oil and Gas Symposium 2017
DOI: 10.2118/185087-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using Water Hammer Characteristics as a Fracture Treatment Diagnostic

Abstract: A water hammer signal is generated at the end of a hydraulic fracturing treatment from the sudden change in fluid velocity in the system. Analysis of water hammer data has been proposed to be a simple, inexpensive diagnostic technique to assess the hydraulic connection between the wellbore, fracture network, and reservoir. Previous studies have reached differing conclusions, suggesting that the water hammer signal can be dominated either by the hydraulic fracture dimensions or by wellbore effects. This study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…However, the fracture lengths estimated under the water-hammer RCI mode exceeded those calculated using alternative techniques (microseismic, electromagnetic imaging, pressure interference testing, and long-term production data analysis), although they were comparable to those derived based on microseismic stimulated reservoirs volumes and the fracture complexity index [16,17]. This is because the mechanisms of water-hammer signals and the associated characteristic parameters (R, C, and I) are complex; furthermore, they are related to factors such as the types of wells completed, the wellbore dimensions, the fluid properties, and the physical properties of the rocks surrounding the fracture [8,18,19].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, the fracture lengths estimated under the water-hammer RCI mode exceeded those calculated using alternative techniques (microseismic, electromagnetic imaging, pressure interference testing, and long-term production data analysis), although they were comparable to those derived based on microseismic stimulated reservoirs volumes and the fracture complexity index [16,17]. This is because the mechanisms of water-hammer signals and the associated characteristic parameters (R, C, and I) are complex; furthermore, they are related to factors such as the types of wells completed, the wellbore dimensions, the fluid properties, and the physical properties of the rocks surrounding the fracture [8,18,19].…”
Section: Introductionsupporting
confidence: 67%
“…A water-hammer signal is a period of pressure pulsation obtained on a surface after fracturing shut-in and contains information regarding the wellbore and hydraulic fracture. Therefore, diagnostic methods based on the wellhead waterhammer pressure are gradually highlighted owing to their cost effectiveness and simplicity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A larger fracture network size would result in a higher water hammer decay. Iriarte [19] suggested that a higher decay rate was associated with increased production. The authors pointed out that additional fractures or a larger fracture network would make the water hammer decay faster.…”
Section: Introductionmentioning
confidence: 99%